Mobilitätsverhalten im ländlichen Raum. Nutzung regionaler Ressourcen und regenerativer Energien für neue Mobilitätsformen der Kleinregion Pielachtal. - Wagner, Isabella (My University, 2013)
Aufgrund rückläufiger Zahlen der jungen Altersgruppen bei gleichzeitiger Alterung der Bevölkerung stellt die wohnortnahe Aufrechterhaltung bestehender Angebote der Grunddaseinsvorsorge - wie Nahversorgungseinrichtungen, Gesundheits- und Bildungsangebote - in ländlichen Räumen gegenwärtig eine besondere Herausforderung dar. Das sind nur einige Faktoren, die das Mobilitätsverhalten beeinflussen. Die individuellen Entscheidungsgründe liegen zusätzlich soziodemographischen, psychologischen und physischen Einflüssen zugrunde. Elektromobilität könnte eine Alternative zum alltäglichen und vielfach priorisierten motorisierten Individualverkehr mit fossilen Antriebsstoffen darstellen. Diese neue Art der Fortbewegung - im Bereich des Individualverkehrs als E-Auto, E-Bike oder Pedelec oder im öffentlichen Personennahverkehr als Hybrid- und E-Bus - ist umweltfreundlich und nachhaltig, vorausgesetzt der Strom wird regenerativ und regional erzeugt.

Rural areas are subject to constant changes and challenges like population increase and decrease, processes of demographic change for example demographic aging while decline of young ages, thinning of public transport infrastructure and services of general interest. All the points, among others, can emerge changes and impairments in mobility behaviour. In addition to psychological and physical factors, the site specific conditions related to mobility behaviour play a major role as well. Furthermore it is affected by sufficient mobility services and services of general interest at the immediate personal environment. The focus of the work is mobility in rural areas, but principally the mobility behaviour of the rural population of the Kleinregion Pielachtal. (How far) Is mobility reconciled with regional development? The importance of mobility in regional development is observed. Using a survey was to determine how the mobility behaviour of the citizens of the Kleinregion Pielachtal is characterized. The results show that the motorcar is dominant to achieve the workplace or apprenticeship place. Especially because of the low public transport network, only a few use public transport. Currently there are hardly incentives to contribute or reduce motorized private transport. Due to the high importance of motorized private transport and drop in supply of public transport the Kleinregion is looking for new possibilities. At the same time fossil fuels are running out and the environment obtained impact. Therefore the Kleinregion sets its focus on alternative and eco-friendly forms of mobility like electric mobility. The south of the Kleinregion Pielachtal has a high proportion of forest. Because of that the Kleinregion would like to use its regional resources. Further resources provide the networks and established concepts.
Keywords: Individualverkehr; Pendlerverkehr; Mobilität; Fahrradverkehr; Verkehrsmittel; Verkehrsmittelwahl; Ländlicher Raum; Regionalentwicklung; Daseinsvorsorge; Bevölkerungsentwicklung; Verkehrsverhalten; Umweltbewusstsein; Mobilitätsverhalten; Alltagsverkehr; Antriebstechnik; Elektromobilität; Erhebung/Analyse